The strengthening relationship between Eurasian snow cover and December haze days in central North China after the mid-1990s - Z. Yin; Z. Yin; H. Wang; H. Wang (Atmospheric Chemistry and Physics, 2018)
The haze pollution in December has become increasingly serious over recent decades and imposes damage on society, ecosystems, and human health. In addition to anthropogenic emissions, climate change and variability were conducive to haze in China. In this study, the relationship between the snow cover over eastern Europe and western Siberia (SCES) and the number of haze days in December in central North China was analyzed. This relationship significantly strengthened after the mid-1990s, which is attributed to the effective connections between the SCES and the Eurasian atmospheric circulations. During 1998–2016, the SCES significantly influenced the soil moisture and land surface radiation, and then the combined underlying drivers of enhanced soil moisture and radiative cooling moved the the East Asia jet stream northward and induced anomalous, anti-cyclonic circulation over central North China. Modulated by such atmospheric circulations, the local lower boundary layer, the decreased surface wind, and the more humid air were conducive to the worsening dispersion conditions and frequent haze occurrences. In contrast, from 1979 to 1997, the linkage between the SCES and soil moisture was negligible. Furthermore, the correlated radiative cooling was distributed narrowly and far from the key area of snow cover. The associated atmospheric circulations with the SCES were not significantly linked with the ventilation conditions over central North China. Consequently, the relationship between the SCES and the number of hazy days in central North China was insignificant before the mid-1990s but has strengthened and has become significant since then.